Rapid and Sensitive Quantification of Ursolic Acid and Oleanolic Acid in Human Plasma Using Ultra-performance Liquid Chromatography-Mass Spectrometry - Stebounova, Larissa; Ebert, Scott M; Murry, Logan T; Adams, Christopher M; Murry, Daryl J (Journal of chromatographic science, 2018)
Abstract Ultra-performance liquid chromatography (UPLC) interfaced with atmospheric pressure chemical ionization mass-spectrometry was used to separate and quantify ursolic acid (UA) and oleanolic acid (OA) in human plasma. UA and OA were extracted from 0.5 mL human plasma using supported liquid extraction and separated utilizing an Acquity UPLC HSS column. The method has been validated for both UA and OA quantitation with a limit of detection of 0.5 ng/mL. The UPLC separations are carried out with isocratic elution with methanol and 5 mM ammonium acetate in water (85:15) as a mobile phase at a flow rate of 0.4 mL/min. The assay was linear from 1 ng/mL to 100 ng/mL for both analytes. The total analysis time was 7 min with the retention times of 3.25 (internal standard), 3.65 (UA) and 3.85 min (OA). Recovery of drug from plasma ranged from 70% to 115%. Analysis of quality control samples at 3, 30 and 80 ng/mL (n = 14) had an intra-day coefficient of variation of 9.9%, 4.3% and 5.5%, respectively. A proof-of-concept study in human patients who consumed apple peels indicates that this analytical method could be applied to clinical studies of UA and/or OA in human subjects.